The chamber for studying rice response to elevated nighttime temperature in field - Chen, Song; Zheng, Xi; Wang, Dangying; Xu, Chunmei; Laza, Ma. Rebecca C.; Zhang, Xiufu (Hindawi Limited, 2013)
An in situ temperature‐controlled field chamber was developed for studying a large population of rice plant under different nighttime temperature treatments while maintaining conditions similar to those in the field during daytime. The system consists of a pipe hoop shed‐type chamber with manually removable covers manipulated to provide a natural environment at daytime and a relatively stable and accurate temperature at night. Average air temperatures of 22.4 ± 0.3°C at setting of 22°C, 27.6 ± 0.4°C at 27°C, and 23.8 ± 0.7°C ambient conditions were maintained with the system. No significant horizontal and vertical differences in temperature were found and only slight changes in water temperatures were observed between the chambers and ambient conditions at 36 days after transplanting. A slight variation in CO2 concentration was observed at the end of the treatment during the day, but the 10‐μmol CO2 mol−1 difference was too small to alter plant response. The present utilitarian system, which only utilizes an air conditioner/heater, is suitable for studying the effect of nighttime temperature on plant physiological responses with minimal perturbation of other environmental factors. At the same time, it will enable in situ screening of many rice genotypes.